PERLINDUNGAN HUKUM BAGI PEREMPUAN DAN ANAK TERHADAP IMPLIKASI YURIDIS PERKAWINAN SIRI: PERSPEKTIF UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM - Jazmine Sukma Sulaeman; M. Abdul Rahman; Asep Nurmansyah; Agus Septima Ridwan (INTELIGENSIA MEDIA, 2026)
Unregistered marriage (siri marriage) is a form of marriage that is valid under religious law but is not recorded with the authorized marriage registrar, thus receiving no legal recognition from the state. This study aims to analyze the juridical implications of siri marriages on the legal status of wives, children, and marital property, as well as to evaluate the effectiveness of Indonesia's positive law instruments in providing legal protection and rights recovery for the aggrieved parties. This research employs a normative juridical method using statutory and conceptual approaches. Legal materials are drawn from Law Number 1 of 1974 as amended by Law Number 16 of 2019 on Marriage and the Compilation of Islamic Law. The findings reveal that siri marriages create significant legal vacuums for wives and children, including the loss of rights to maintenance, joint marital property, and inheritance. Existing legal protection is reactive rather than preventive, relying on the itsbat nikah mechanism at the Religious Court, which is not easily accessible for underprivileged communities. The state must strengthen the marriage registration system as a comprehensive legal protection instrument.